Higher-derivative Schwinger model - Amaral, R. L.P.G.; Belvedere, L. V.; Lemos, N. A.; Natividade, C. P. [UNESP] (American Physical Society (APS), 1993)
Using the operator formalism, we obtain the bosonic representation for the free fermion field satisfying an equation of motion with higher-order derivatives. Then, we consider the operator solution of a generalized Schwinger model with higher-derivative coupling. Since the increasing of the derivative order implies the introduction of an equivalent number of extra fermionic degrees of freedom, the mass acquired by the gauge field is bigger than the one for the standard two-dimensional QED. An analysis of the problem from the functional integration point of view corroborates the findings of canonical quantization, and corrects certain results previously announced in the literature on the basis of Fujikawa's technique. © 1993 The American Physical Society.